PERBANDINGAN HASIL BELAJAR KIMIA MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN THINK TALK WRITE - Nadya Dirma Wahyuni; Amrul Bahar; Dewi Handayani (ALOTROP, 2017)
[COMPARISON FROM LEARNING OUTCOMES OF PROBLEM BASED LEARNING MODELS AND THINK TALK WRITE  MODELS ]               Each learning model has advantages and disadvantages in every process.This research intent to know the difference student studying result on chemical learning among brazes that utilize learning model Problem Based Learning (PBL)  with class that utilize learning model Think is Write's Talc (TTW)  on jurisdictional material – chemical base law at class X SMA Negeri  10  Kota Bengkulu's . This research constitute quasi's experiment. Students learned result on observational it is seen from pretest's point and posttest difference. On class that utilize Problem Based Learning (PBL) model , increasing average value from student kognitiv as big as 49,23. Meanwhile class that utilize Think is Write's Talc (TTW) model ,  increasing average value learned student kognitiv as big as 56,33.   Hypothese  was tested by use of t test (? = 0,01) to result at t test  = 3,53 < t table  = 2,38. Research result to point out that are distinctive result  that significan among between class that utilize Problem Based Learning (PBL ) model and class that utilize Think is Write's Talk (TTW) model.